In a class by himself eaudiobook - Peirce, Lincoln (Big Nate, 2010)
Soon to be an animated series from Nickelodeon! "Big Nate is funny, big time."Jeff Kinney, author of Diary of a Wimpy Kid For fans of the hilarious Diary of a Wimpy Kid series: Get ready to meet Big Nate! In the first novel in the New York Times bestselling series, Big Nate is in a class by himself! Nate knows he's meant for big things. REALLY big things. But things don't always go your way just because you're awesome. Nate barely survives his dad's toxic oatmeal before rushing off to school—minus his lunch. He body slams the no-nonsense principal. He accidentally insults his least favorite teacher, the horrifying Mrs. Godfrey (aka Godzilla). And school has barely started! Trouble always seems to find him, but Nate keeps his cool. He knows he's destined for greatness. A fortune cookie told him so. Here comes BIG NATE, accidental mischief maker and definitely NOT the teacher's pet.